The Noken System as a Symbol of the Supreme Deliberation of Indigenous Peoples in Papua Anthropological Study of Law and Constitutional Law - Handayani, Emy; Sri Hardjanto, Untung (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
An electoral system used specifically for a number of districts in the Central Highlands region of Central Papua and Mountain Papua, Indonesia is called the noken system. The noken system is directly related to traditional leaders/traditional elders/tribal chiefs which of course is related to several reasons for holding noken elections both geographically, human resources, socio-culturally. In the tradition of indigenous Papuans, noken is interpreted in the value of elections by making mutual agreements and establishing intact / support for certain candidates with consensus deliberation. In other words, the noken system is a symbol of the highest deliberation for opinion determination in Papua without secrets and is more concerned with deliberation in tribal communities in Papua. The study of Legal Anthropology focuses on the socio-culture of indigenous Papuans, if in making decisions collectively collegially both in life, and in social relations both ideas, ideas in deliberation become absolute decisions, and are officially declared by their tribal chiefs (bigman), because traditional Papuan / inland communities adhere to traditional politics (bigman). So that noken is a cultural object, a community routine that is interpreted in electoral values by making mutual agreements, voting as a whole/supporting certain candidates with consensus deliberation. Thus, the use of noken means that Papuan indigenous elements are respected and obedient people to participate in elections, and to position noken to respect the entire life of indigenous Papuans. This reality underlies the opinion that noken is part of the local wisdom of indigenous Papuans who should be respected, fostered, maintained, preserved, cared for and maintained in their existence to maintain customary law in indigenous Papuans. The study of Constitutional Law focuses on a regulation to determine the noken election to be valid, with the issuance of Constitutional Court Decree Number 47-48 / PHPU-A-VII / 2009 concerning the Noken System Election in Papua. The Constitutional Court understands and appreciates the cultural values that live in indigenous Papuans that are distinctive in elections with the "Citizen Agreement" system that based on the agreement of the community understand noken as a change in object, namely the form of the KPU ballot box replaced with the form of hanging noken and contains philosophical meanings namely opening, filling and binding in the political practice of elections held on indigenous Papuans